2010
DOI: 10.1111/j.1468-2494.2010.00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal and dermal changes in response to various skin rejuvenation methods

Abstract: During the last years, a number of new devices have been developed to improve the dermal and epidermal signs of photo- and chronological skin ageing. There are well-established ablative and non-ablative skin resurfacing options using different lasers and light sources, but side effects have been observed frequently. A recently developed photorejuvenation method using non-thermal stimulation of skin cells with low energy and narrow band light has been termed photomodulation. Light emitting diodes are the ideal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 144 publications
(159 reference statements)
0
8
0
3
Order By: Relevance
“…Photomodulation was the photobiostimulatory effect originally developed for NASA plant growth experiments 300 in space, and was later discovered efficacy of promoting cell activity like wound healing and photorejuvenation. 16,17 NASA found that the optimal light wavelengths (proven in prior studies of laser and LED light) for photobiostimulation included 680, 730, and 880 nm 16 , which are all included in the IPL wavelength spectrum used for treatment. We presumed that the photomodulation stimulates acinar cell activity, thus improving MG microstructure.…”
Section: Discussionmentioning
confidence: 99%
“…Photomodulation was the photobiostimulatory effect originally developed for NASA plant growth experiments 300 in space, and was later discovered efficacy of promoting cell activity like wound healing and photorejuvenation. 16,17 NASA found that the optimal light wavelengths (proven in prior studies of laser and LED light) for photobiostimulation included 680, 730, and 880 nm 16 , which are all included in the IPL wavelength spectrum used for treatment. We presumed that the photomodulation stimulates acinar cell activity, thus improving MG microstructure.…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic aging process is understood as natural and inevitable, related to genetic factors and functional changes accumulated with time. 1,13,14 Clinically, the aged skin appears dry, wrinkled, flaccid, and with the presence of nonmalignant neoplastic lesions. The extrinsic aging process is determined by harmful external factors and can be avoided.…”
Section: S K In Ag Ingmentioning
confidence: 99%
“…These changes occur due to the combination of intrinsic and extrinsic factors. The intrinsic aging process is understood as natural and inevitable, related to genetic factors and functional changes accumulated with time . Clinically, the aged skin appears dry, wrinkled, flaccid, and with the presence of nonmalignant neoplastic lesions.…”
Section: Skin Agingmentioning
confidence: 99%
“…HSP70 (heat shock protein 70) is a crucial trigger point for scar‐free wound healing as well as the treatment of neoplastic skin using photodynamic therapy and ablative fractional lasers . Subsequently, the spatiotemporal healing process was analyzed in vivo, and threshold values (spot size 250 μm, coverage < 50 %, fluence < 100 mJ for the Quantel Exelo 2 system) for safe and effective treatment were determined . These were then confirmed by optical coherence tomography and reflectance confocal microscopy .…”
Section: Fractional Photothermolysismentioning
confidence: 99%